2016
DOI: 10.1039/c6ra13021f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of semiaromatic polyamides with dicyclohexane units

Abstract: The resultant semiaromatic polyamides showed excellent mechanical properties, superior thermal properties and good processability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…These results indicated that the T d and T max decreased with the introduction of the increasing weight percentage of long alkyl segments from polyamide salt. This can be ascribed to the relatively low stability of aliphatic methyl at high temperature . However, the thermal stability was virtually maintained, with the incorporation of BABA/SA salt into the polymeric backbone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that the T d and T max decreased with the introduction of the increasing weight percentage of long alkyl segments from polyamide salt. This can be ascribed to the relatively low stability of aliphatic methyl at high temperature . However, the thermal stability was virtually maintained, with the incorporation of BABA/SA salt into the polymeric backbone.…”
Section: Resultsmentioning
confidence: 99%
“…This can be ascribed to the relatively low stability of aliphatic methyl at high temperature. 36 However, the thermal stability was virtually maintained, with the incorporation of BABA/SA salt into the polymeric backbone. From the result of TGA analysis, the new series of copolyamides show good thermal stability (onset degradation temperature is over 350 C), which is adequate for most common applications.…”
Section: Thermal and Crystalline Properties Of Baba-sa Salt And Pa6-bmentioning
confidence: 99%
“…The polarity of anionic groups confers water solubility on dyes that bear these anionic groups. Unlike these traditional dyes, the polymeric black dye is a kind of polyampholyte, and its solubility was affected not only by the anionic groups but also by the molar ratio of the cationic to anionic groups . The sulphonic acid group (–SO 3 H) ionises to anionic sulphonate (–SO3) at pH > 1, and the amounts of protonated amino groups in the PVAm are related to the external pH .…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al synthesized the novel semi-aromatic polyamide with long carbon chain diamines; its melting point was about 310 °C [11]. Additionally, in terms of changing the crystal structures of semi-aromatic polyamide, alicyclic was introduced into the molecular chain of semi-aromatic polyamide by Yan et al (T g = 217.2-236.9 °C) [12], azo units by Huang et al [13], triazole units by Ivanysenko et al (T g = 161 °C) [14], hyperbranched units by Shabbir et al (T g = 138-198 °C) [15], sulphone groups by Shabanian et al [16] and by Li et al (T g = 121-177 °C) [17], or long carbon chain diamines by Zhang et al (T g = 163-203 °C) [18] into the polymer's chain to improve the resin's solubility.…”
Section: Introductionmentioning
confidence: 99%